Minat Mahasiswa Terhadap Jasa Taksi Online - Sidjabat, Sonya (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2018)
The purpose of this research is to analyze the impactsof promotion and service quality on the studentâs demand for online serviced taxi. Taxi online itself is a kind of application-based service in public transportation.In this research, the writer took randomly 379 students of Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti as respondents. The collected data then were processed and analysed by using statistical method, the multiple linear regression. The research result concluded that the promotion and the quality of service have significant and positive impactsfor the students to order the onlined servicing taxi.